Modul Matematika Bilingual dengan Pendekatan Problem Based Instruction (PBI) Berbasis Kemampuan Soft Skill Sebagai Pengembangan Perangkat Pembelajaran - Fera Aprianti; Farida Farida; Rizki Wahyu Yunian Putra; Nurhasanah Leni; Ahmad Sodiq (Nabla Dewantara, 2021)
: Research Objectives To determine the feasibility of learning devices and learners' response to learning devices bilingual math modules based on soft skills. The research model used in research development is a type of research and development (R&D). This study did not reach mass production, only tested the feasibility of the product based on validator assessment, knowing the response of learners and knowing the effectiveness of the product. Data collection techniques with interviews, Posttest Questionnaires to find out the results of learners' learning towards the ability tested in accordance with the criteria of success indicators (IK) used. Instruments for data collection in the form of interviews, questionnaires, documentation tests. Data analysis techniques are, in the form of qualitative descriptive and descriptive quantitative. The result of the research that the development of bilingual math module peoruk produced is very feasible. The response of manarik learners to bilingual math modules with PBI approach based on soft skills.